Perceived level of stress in patients with acute coronary syndrome in Sri Lanka: associations and short-term outcomes - A. T. Matthias; D. K. N. de Silva; J. Indrakumar; S. B. Gunatilake (Sri Lanka College of Internal Medicine, 2023)
Background: Chronic stress is a known risk factor for cardiovascular disease. This study sought to determine the association between the 'perceived level of stress' in patients with acute coronary syndrome (ACS) and its short-term outcome. This is the first study done on the perceived level of stress in patients with ACS in Sri Lanka. Methods: A total of 313 ACS patients from the Professorial Unit of the Colombo South Teaching Hospital completed the Perceived Stress Scale-10. The scale assesses the stress perceived by the patient based on ten questions. The sum of scores ranges from 0-40. High stress was defined as scores of 20 or above. Results: High-stress levels were found in 238 (76%) patients and low stress in 75 (24%). There was no difference in the level of stress perceived by males and females (p=.5). Stress levels did not change the nature of the presenting complaint: typical chest pain versus another complaint (p=.09). Patients with high-stress levels presented early (within 12 hours) to the hospital (p<.05). There was no difference in the stress levels of patients presenting with different types of ACS: ST-Elevation Myocardial Infarction (STEMI), non-ST-elevation myocardial infarction (NSTEMI), or unstable angina (UA) (p=.147). Conclusions: High-stress levels were seen in most patients with ACS and steps need to be taken to reduce stress. The stress levels did not influence the severity or the type of ACS. Patients with high-stress levels were likely to present early to the hospital.